Drying of a plasmid containing formulation: chitosan as a protecting agent - Mohajel, Nasir (BioMed Central, 2012)
BACKGROUND: The purpose of the study. Along with research on development of more efficient gene delivery systems, it is necessary to search on stabilization processes to extend their active life span. Chitosan is a nontoxic, biocompatible and available gene delivery carrier. The aim of this study was to assess the ability of this polymer to preserve transfection efficiency during spray-drying and a modified freeze-drying process in the presence of commonly used excipients. METHOD: Molecular weight of chitosan was reduced by a chemical reaction and achieved low molecular weight chitosan (LMWC) was complexed with pDNA. Obtained nanocomplex suspensions were diluted by solutions of lactose and leucine, and these formulations were spray dried or freeze dried using a modified technique. Size, polydispersity index, zeta potential, intensity of supercoiled DNA band on gel electrophoresis, and transfection efficiency of reconstituted nanocomplexes were compared with freshly prepared ones. RESULTS AND MAJOR CONCLUSION: Size distribution profiles of both freeze dried, and 13 out of 16 spray-dried nanocomplexes remained identical to freshly prepared ones. LMWC protected up to 100% of supercoiled structure of pDNA in both processes, although DNA degradation was higher in spray-drying of the nanocomplexes prepared with low N/P ratios. Both techniques preserved transfection efficiency similarly even in lower N/P ratios, where supercoiled DNA content of spray dried formulations was lower than freeze-dried ones. Leucine did not show a significant effect on properties of the processed nanocomplexes. It can be concluded that LMWC can protect DNA structure and transfection efficiency in both processes even in the presence of leucine.